Effects of Iranian healthcare transformation plan on discharge against medical advice rate and related factors in 2012 and 2016 - Hossein Jabbari Beyrami; Ali Taghizadieh; Saber Azami-Aghdash; Reza Piri; Mohammad Naghavi-Behzad (BMJ Open)
Objective Discharge against medical advice (DAMA) is a critical problem in hospitals and has several consequences for healthcare systems. The aim of this study was to determine and compare the rate of DAMA and its related factors before and after executing the healthcare transformation plan (HTP) in Iran.Methods In a two-phase, cross-sectional study, the DAMA information of 200 patients in 2016 (after HTP) and the patients of a previous study in 2012 (before HTP) was compared. Samples were randomly selected from the main referral centre in the north-west of Iran. Data were collected using a validated and reliable questionnaire and analysed using the SPSS V.16 software.Results In the post-HTP plan period, the rate of DAMA was 3.9%, while this rate was 5.49% in 2012 (p=0.029). A total of 15% (108 out of 721) of patients in the postreform group and 13.5% (101 out of 747) in the prereform group were rehospitalised (p=0.411). The three main categories of reasons for DAMA in 2012 and 2016 were as follows: patient-related factors, 27% vs 45%; staff-related factors, 33% vs 30%; and hospital-related factors (basic amenities), 40% vs 25%. In both periods, the average scores of patient satisfaction were almost the same; however, satisfaction regarding environmental and human factors in hospitals had changed significantly after HTP (p<0.05).Conclusions There was a decrease in the rate of DAMA after HTP in Iran. Considering DAMA as a multifactorial phenomenon, this might be due to the higher relative satisfaction after HTP, indicating an increase in public confidence in general hospitals.